2014
DOI: 10.1260/1757-482x.6.1.49
|View full text |Cite
|
Sign up to set email alerts
|

CFD Modelling of the Effects of Operating Parameters on the Spreading of Liquids on a Spinning Disc

Abstract: A novel dry slag granulation process based on a spinning disc is being developed by CSIRO. This process utilises centrifugal force to break up molten slag into droplets, which are then quenched into solidified granules by a flow of cold air. In this process the sensible heat of slag is recovered as hot air. In the present work, a previously developed steady-state, two-dimensional and multiphase CFD model was applied to perform parametric numerical experiments to investigate the effects of a number of parameter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
6
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(8 citation statements)
references
References 13 publications
2
6
0
Order By: Relevance
“…Furthermore, as mentioned in the preceding section, the average ratio (4.25) between the arithmetic mean diameter of slag particles and the liquid film thickness for centrifugal granulation of molten slag-metal mixture is close to the value of 4.0 reported in the literature for the single slag phase [21]. In addition, the authors also conducted a comparison between the simulation outcomes of this research and a theoretical model (Equation ( 9)) reported in the literature regarding the flow of a liquid film over a spinning disc [19], which reads h = 0.479 G 0.336 µ 0.275 Ω 0.612 R 0.56 ρ 0.612 (9) where h is the liquid film thickness at the edge of the spinning cup (mm); G is the liquid feeding rate (kg•min −1 ); µ is the liquid dynamic viscosity (Pa•s); R is the radius of the disc or inner radius of the spinning cup (mm); Ω is the spinning speed (RPM); and ρ is the liquid density (kg•m −3 ).…”
Section: Model Validationsupporting
confidence: 79%
See 1 more Smart Citation
“…Furthermore, as mentioned in the preceding section, the average ratio (4.25) between the arithmetic mean diameter of slag particles and the liquid film thickness for centrifugal granulation of molten slag-metal mixture is close to the value of 4.0 reported in the literature for the single slag phase [21]. In addition, the authors also conducted a comparison between the simulation outcomes of this research and a theoretical model (Equation ( 9)) reported in the literature regarding the flow of a liquid film over a spinning disc [19], which reads h = 0.479 G 0.336 µ 0.275 Ω 0.612 R 0.56 ρ 0.612 (9) where h is the liquid film thickness at the edge of the spinning cup (mm); G is the liquid feeding rate (kg•min −1 ); µ is the liquid dynamic viscosity (Pa•s); R is the radius of the disc or inner radius of the spinning cup (mm); Ω is the spinning speed (RPM); and ρ is the liquid density (kg•m −3 ).…”
Section: Model Validationsupporting
confidence: 79%
“…Using the VOF multiphase flow model, Wang et al [18] numerically simulated the flow of a continuous free surface film on a spinning disc and determined the slag film thickness distribution in the direction of the disc radius. Pan et al [19,20] performed numerical simulations using an established CFD model to explore the effect of various parameters on the liquid film thickness at the edge of the disc. By conducting a regression analysis to correlate the experimentally measured mean slag particle diameter reported by Liu et al [21] with the slag film thickness predicted through CFD model simulations, Zhang et al [22] found that the mean diameter of slag particles is approximately four times the slag film thickness at the cup's edge.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, some numerical simulations were carried out on the centrifugal granulation. Pan et al [26,27] adopted a CFD model to simulate free surface flow of liquid slag on a spinning disc and discussed the effects of operating parameters on the liquid spreading. Wang et al [28] developed a theoretical analysis for free-surface flow on the disc, and it was found that the film thickness distribution of molten slag was mainly determined by liquid volume flow rate, rotary speed of atomizer and viscosity.…”
Section: Introductionmentioning
confidence: 99%
“…This modelling work is a key component of our strategy for process design, optimisation and scale-up. Some of the early results on simulation of free surface flow and heat transfer between molten slag and spinning disc have been published [49,50]. The findings from these and subsequent studies have quantified the effects of slag temperature, tapping rate and spinning speed on slag atomisation and heat transfer between phases.…”
Section: Process Simulation Using Computational Fluid Dynamicsmentioning
confidence: 99%